1999
DOI: 10.1097/00005072-199909000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Myoblasts in SCID Mice as a Potential Muscular Model for Myotonic Dystrophy

Abstract: Myotonic dystrophy (DM), the most frequent hereditary myopathy in adults, is characterized clinically by muscle weakness, myotonia, and systemic symptoms. Although the specific genetic basis for DM has been established, less is known about the cellular defects responsible for its pleiotropic manifestations. DM pathogenesis studies are presently limited due to the absence of animal models. In the present study, we transplanted myoblasts of DM patients into the Tibialis anterior of Severe Combined Immunodeficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…[55][56][57][58] In the present study, human FSHD myoblasts were injected into immunodeficient Rag mice, a validated mouse model for the analysis of muscle regeneration in the context of xenogenic MT. The implantation results we obtained were close to that reported previously [47][48][49] and confirmed that myoblasts prepared from unaffected FSHD muscles, even used at the 6th and 7th passages, take part into in vivo muscle regeneration. The overall number of dystrophin-positive fibers was inferior to that reported previously in immunocompetent models of muscular dystrophies in the context of syngenic or allogenic MT.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[55][56][57][58] In the present study, human FSHD myoblasts were injected into immunodeficient Rag mice, a validated mouse model for the analysis of muscle regeneration in the context of xenogenic MT. The implantation results we obtained were close to that reported previously [47][48][49] and confirmed that myoblasts prepared from unaffected FSHD muscles, even used at the 6th and 7th passages, take part into in vivo muscle regeneration. The overall number of dystrophin-positive fibers was inferior to that reported previously in immunocompetent models of muscular dystrophies in the context of syngenic or allogenic MT.…”
Section: Discussionsupporting
confidence: 90%
“…At 1 month after MT, the expression of human proteins validated the implantation of human cells into mouse muscle fibers. 16,[47][48][49] Human dystrophin was observed in all cell-injected muscles, and was absent from muscles injected with a saline solution (Table 3, Figure 5). No significant differences were observed between muscles receiving FSHD or control myoblasts (P40.8).…”
Section: In Vivo Regenerating Abilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Currently explanations include: deficiency of the DM protein kinase 14 ; effect of expanded CTG repeats on neighboring genes [15][16][17][18] ; interference of the mutant DM protein kinase transcripts with others transcripts (trans RNA interference) 19 . Studies that are in progress look for new transgenic models that may more closely resemble clinical DM and that provide also a model for anticipation 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The cells were transplanted into the TA muscle of immunodeficient severe combined immuno deficient (SCID) mice that tolerate xenograft. 17 The mice were killed a month later. The human cells were able to fuse with the mouse muscle fibers and as shown in Figure 2c and d, eGFP expression was visible in muscle fibers.…”
Section: Transplantation Of Human Primary Mpcs Expressing Egfpmentioning
confidence: 99%